Celebrity Cake Branding as the Initiators of Nowadays Cake - Rostika Yuliani; Susanne Dida; Nisa Eka Nastiti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2020)
The development of business culinary in Bandung city invited Indonesian national celebrities to invest in cake shops. Laudya Cynthia Bella, with her Bandung Makuta, and Ananda Omesh, with his Bandung Kunafe, were the initiators. The research aimed to assimilate the branding methods of Bandung Makuta and Bandung Kunafe as nowadays cakes. The research used a combination between a qualitative method and a study-case approach. The data was collected by performing interviews, observation, literature review, and online data gathering. The research found that branding activity run by Bandung Makuta and Bandung Kunafe in the form of advertising, marketing, public relations, and special events was considered successful in making residents and tourists of Bandung visit Bandung city and purchase the products. Taglines #initehngangenin (#itismemorable) and #lembutpisaneuy (#itisalsomoist) promoted by Bandung Makuta and Bandung Kunafe, respectively, triggered the customers to be more intrigued by the products. The research recommended that Bandung Makuta and Bandung Kunafe start to innovate and modify their products, notably the form, taste, and package